Rekonstruksi Model Pedagogi Pendidikan Anak dalam Tafsir Al-Mishbah: Analisis Tematik QS. Luqman 12–19 dan Relevansinya di Era Kontemporer - Ngadiman Ngadiman; Zaedul Khaer; Abdus Syukur (Alpatih Harapan Semesta, 2026)
Child education in Islam is not limited to knowledge transmission but encompasses the development of spiritual awareness, moral character, and social responsibility. This study aims to reconstruct a pedagogical model of child education based on Muhammad Quraish Shihab’s interpretation of QS. Luqman 12–19 in Tafsir Al-Mishbah and to examine its relevance in the contemporary era. The study employed a qualitative approach using library research and thematic (maudhu’i) analysis. Data were analyzed through four stages: identification of relevant verses, examination of interpretative meanings, categorization of pedagogical values, and synthesis into a conceptual framework. The findings reveal three interconnected dimensions of Islamic child pedagogy: (1) tawhid as the foundation of spiritual consciousness, (2) akhlaq as the core of character formation, and (3) a dialogic-affective approach as the primary educational method. The novelty of this study lies in the integrative reconstruction of a Qur’anic pedagogical model that combines spiritual, moral, and methodological dimensions, offering a relevant framework for contemporary Islamic education in addressing the challenges of the digital era.